"Do I Read it? No". Knowledge Utilisation in Child Welfare Decisions. Issue 3 (3rd July 2022) - McCafferty, Paul
ABSTRACT: Much as one would like to be able to base permanency decisions on the solid ground of empirical findings and objective knowledge, the nature of child abuse precludes this possibility. In the absence of any unitary knowledge base, it is important to know what knowledge social workers use to inform their permanency decisions. This article presents findings from an exploratory in-depth qualitative research project with the objective of exploring the knowledge that social workers use to make decisions regarding permanency arrangements for Looked after Children. This research formed part of my Doctorate in Childhood Studies at Queen's University Belfast. Thinking aloud-protocols and semi-structured interviews, in conjunction with a specifically constructed vignette, were used as an innovative methodology to explore the knowledge used to make permanency decisions by experienced practitioners in a local authority in Northern Ireland. A thematic analysis was used to structure the findings. An adapted model of knowledge was used to structure the themes which was based on Drury-Hudson (1997. A model of professional knowledge for social work. Australian Social Work, 50 (3), 35–44) and Pawson et al's. (2003) model of knowledge. The findings show that organisational knowledge and practitioner knowledge were privileged almost exclusively over research, theory and service user knowledge. Findings also reveal that using these two sources of knowledge led to overwhelmingly protectionist oriented decisions, significantly affecting the care trajectory of the child in the vignette. Recommendations are made with the aim of improving the extent and depth of practitioner knowledge in this field, thus helping to increase the robustness, consistency and defensibility of decisions taken.